The Mechanism Underlying of Long-Term Stable Indigo Reduction State in Indigo Fermentation Using Sukumo (Composted Polygonum tinctorium Leaves) - Tu, Zhihao; Lopes, Helena de Fátima Silva; Narihiro, Takashi; Yumoto, Isao (Frontiers in Microbiology, 2021)
Indigo fermentation fluid maintains its indigo-reducing state for more than 6 months under open-air. To elucidate the mechanism underlying the sustainability of this indigo reduction state, three indigo fermentation batches with different durations for the indigo reduction state were compared. The three examined batches exhibited different microbiota and consisted of two phases. In the initial phase, oxygen-metabolizing-bacteria derived from sukumo established an initial network (phase 1). With decreasing redox potential (ORP), the initial network was replaced by obligate anaerobes (mainly Proteinivoraceae). Approximately 1 month after the indigo reduction, the predominating obligate anaerobes were decreased, and Amphibacillus and Polygonibacillus, which can decompose macromolecules derived from wheat bran, were predominantly observed, and the change of microbiota became slow (phase 2). This is probably due to the change in predominant substrates; from substrates derived from sukumo to wheat bran. This study provides new insights into changes in bacterial flora from the initial phase to the stable phase (phase 1 → 2), suggesting that the seed bacteria in sukumo thrive using endogenous substrates in sukumo. Subsequently, the bacterial community that appeared first was replaced by anaerobic bacteria in concomitance with a decrease in ORP. This initial bacterial community consumed the substrates derived from sukumo and substrates derived from initial events (i.e., heat treatment and decrease in ORP) in the fermentation within approximately one month. Finally, the indigo-reducing ecosystem changed to a wheat bran-based bacterial community that changed slowly with the fermentation period.